2017
DOI: 10.1021/acs.inorgchem.6b02695
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Penetrant Manganese Superoxide Dismutase (MnSOD) Mimic Is Able To Complement MnSOD and Exerts an Antiinflammatory Effect on Cellular and Animal Models of Inflammatory Bowel Diseases

Abstract: Inorganic complexes are increasingly used for biological and medicinal applications, and the question of the cell penetration and distribution of metallodrugs is key to understanding their biological activity. Oxidative stress is known to be involved in inflammation and in inflammatory bowel diseases for which antioxidative defenses are weakened. We report here the study of the manganese complex Mn1 mimicking superoxide dismutase (SOD), a protein involved in cell protection against oxidative stress, using an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 36 publications
(98 citation statements)
references
References 108 publications
9
89
0
Order By: Relevance
“…However,c areful inspection of the EPR spectra on the edge of the 6-lines signal show that the signature of am ixture of Cu(Ab) and 1 + + perfectly matches the hyperfine features of [Cu(L)] + (complex noted 2 2 + + )r ecorded under the very same conditions (Figure 2). Note:i )that the 9-GHz EPR signature of 1 + + gives a broad signal with no hyperfine structure in the g = 2r egion,a s expected for this highly distortedM n II species [13,15] (Figure S2); ii)asap arallel experiment, the removal of Cu from the Ab peptide by the ligand LH has been recorded by EPR ( Figures S3), and iii)the metal swap experiment has also been followed by UV/Vis ( Figure S4), the data obtained matching the EPR results. Affinity of Mn II for LH has been evaluated by direct titration monitored by UV/Vis ( Figure S5) leading to an apparent affinity constant of 1.3 10 6 m À1 (pH 7.1, 100 mm HEPES) in line with previousm easurement by calorimetry.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…However,c areful inspection of the EPR spectra on the edge of the 6-lines signal show that the signature of am ixture of Cu(Ab) and 1 + + perfectly matches the hyperfine features of [Cu(L)] + (complex noted 2 2 + + )r ecorded under the very same conditions (Figure 2). Note:i )that the 9-GHz EPR signature of 1 + + gives a broad signal with no hyperfine structure in the g = 2r egion,a s expected for this highly distortedM n II species [13,15] (Figure S2); ii)asap arallel experiment, the removal of Cu from the Ab peptide by the ligand LH has been recorded by EPR ( Figures S3), and iii)the metal swap experiment has also been followed by UV/Vis ( Figure S4), the data obtained matching the EPR results. Affinity of Mn II for LH has been evaluated by direct titration monitored by UV/Vis ( Figure S5) leading to an apparent affinity constant of 1.3 10 6 m À1 (pH 7.1, 100 mm HEPES) in line with previousm easurement by calorimetry.…”
mentioning
confidence: 92%
“…Indeed, while LH is toxic towards epithelial cells as a free ligand, the toxicity is abolished when LH is bound to Mn(II) (in complex 1 + ). [15] Hence, the use of a potentially toxic ligand to remove Cu(II) from Aβ is replaced by the use of 1 + which is non-toxic and leads to the very same retrieval effects. It is worth noting here that we also studied another Mn(II) SOD mimic [Mn(IPG)] (IPG = N-[(1-methyl-imidazol-2-yl)methyl]-N-(2-pyridylmethyl)glycinate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Following on, the manganese (II) SOD mimics Mn1 ( Figure 1) was studied in cells and in vivo. 12,23 Its ability to limit ROS flow in cells was demonstrated in activated macrophages. 23 In addition, its study in a cellular model of inflammatory diseases demonstrated the ability of the complex to limit oxidative stress and inflammatory reaction in a cellular model of inflammatory bowel diseases at a concentration of incubation of 100 µM.…”
mentioning
confidence: 99%
“…23 In addition, its study in a cellular model of inflammatory diseases demonstrated the ability of the complex to limit oxidative stress and inflammatory reaction in a cellular model of inflammatory bowel diseases at a concentration of incubation of 100 µM. 12 At this concentration, Mn1…”
mentioning
confidence: 99%